Question 4(Multiple Choice Worth 1 points)
(07.02 MC)
An equation is shown below:
4(2x - 3) = 1
Which of the following correctly shows the steps to solve this equation?
Step 1: 6x - 7 = 1; Step 2: 6x = 8
Step 1: 6x + 1 = 1; Step 2: 6x = 0
Step 1: 8x - 12 = 1; Step 2: 8x = 13
Step 1: 8x - 3 = 1; Step 2: 8x = 4

Respuesta :

Answer:

Step 1: 8x - 12 = 1; Step 2: 8x = 13

Step-by-step explanation:

Given equation:

4(2x - 3) = 1

Step 1: open the parenthesis

4(2x - 3) = 1

8x - 12 = 1

Step 2: collect like terms

8x - 12 = 1

8x = 1 + 12

8x = 13

step 3: divide both sides by the coefficient of x

8x = 13

x = 13/8

The correct steps to solve the equation:

Step 1: 8x - 12 = 1; Step 2: 8x = 13

ACCESS MORE